TRPV1 channel in spermatozoa is a molecular target for ROS-mediated sperm dysfunction and differentially expressed in both natural and ART pregnancy failure - Swain, Nirlipta; Samanta, Luna; Goswami, Chandan; Kar, Sujata; Majhi, Rakesh Kumar; Kumar, Sugandh; Dixit, Anshuman (Frontiers in Cell and Developmental Biology, 2022)
Bi-directional crosstalk between Ca2+ signaling and ROS modulates physiological processes as a part of a regulatory circuit including sperm function. Role of transient receptor potential vanilloid 1 (TRPV1) in this regard cannot be undermined. This is the first report demonstrating Ca2+-sensitive TRPV1 channel to be under-expressed in spermatozoa of normozoospermic infertile males with high ROS (idiopathic infertility and unilateral varicocele). To study the effect of TRPV1 in determining the fertility outcome, we compared the expression profile of TRPV1 in spermatozoa of male partners who achieved pregnancy by natural conception (NC+, n=10) or IVF (IVF+, n=23) or ICSI (ICSI +, n= 9) and their respective counterparts with failed pregnancy NC- (n=7), IVF-( n= 23), ICSI- (n=10), by both immunocytochemistry and flow-cytometry. Reduced expression of TRPV1 in sperm of IVF+/- and ICSI+/- men with respect to NC+ men imply its role in mediating a successful fertilization. Unsuccessful pregnancy outcome with an underexpression of TRPV1 in sperm of NC-/IVF-/ICSI- men, suggests its role in conception and maintenance of pregnancy. Since ROS is regarded as one of the major contributors in sperm dysfunction, the effect of H2O2 +/- TRPV1 modulators (RTX/ iRTX), on acrosomal reaction and calcium influx was evaluated to confirm TRPV1 as redox sensor in human sperm. A significant increment in the percentage of acrosome reacted spermatozoa along with augmented Ca2+ -influx was observed after H2O2 treatment, both in presence or absence of TRPV1 agonist Resiniferatoxin (RTX). The effect was attenuated by TRPV1 antagonist Iodoresiniferatoxin (iRTX), indicating the involvement of TRPV1 in mediating H2O2 response. Enhancement of motility and triggering of acrosomal reaction post TRPV1 activation, suggested that disruption of these signalling cascades in vivo, possibly due to down regulation of TRPV1 in these sub fertile males. Bioinformatic analysis of the crosstalk between TRPV1 with fertility candidate proteins (reported to influence IVF outcome), revealed cell death and survival, cellular compromise, and embryonic development to be the primary networks affected by anomalous TRPV1 expression. We therefore postulate that TRPV1 can act as a redox sensor and its expression in spermatozoa may serve as a fertility marker.